PENERAPAN PERMAINAN ENGKLEK FRUIT SEBAGAI STIMULASI KEMAMPUAN MOTORIK KASAR ANAK USIA DINI - Sam, Fira Khoiriyah; Pramono, Pramono; Astuti, Wuri (PG PAUD Universitas Negeri Surabaya, 2021)
This study was carried out aimed at analyzing the application of the traditional fruit crank game as stimulation, gross motor skills of early childhood. This research uses library research, which is a research procedure that studies data collection by collecting data from various documents. The most prominent character education values in the animated series The Adventures of Si Unyil are honesty, respect and courtesy, generous, helpful, confident, creative. By using this traditional game, children's gross motor skills can be trained by helping children to control their bodies and themselves, and can train children to read body movements, move their bodies, and or most importantly, train their dexterity and agility in fruit crank games so that children can train their body agility in doing something.